Analisis Kompetitif Industri Pertahanan Nasional: Prospek dan Tantangan Pasca Revisi Undang-Undang Nomor 16 Tahun 2012 tentang Industri Pertahanan - Adrianus Revi Dwiguna; Athor Subroto; Achmad Sanusi (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2022)
This study aims to examine the developments and dynamics, as well as the challenges of the national defense industry, after the revision of Law No. 16 of 2012 on the Defense Industry, through Law No. 11 of 2020 on Job Creation. This qualitative research uses interviews and literature studies as data collection methods sourced from primary and secondary data, and analyzed using a competitive strength framework. As a result, these regulatory changes are relatively able to have a positive impact, especially regarding the increase in the number of entities and opportunities for financing the defense industry through investment mechanisms by the private sector. In addition, the expansion of the role of BUMS in the supply chain of the national defense industry has also opened up opportunities for technology development and the fulfillment of industrial needs which are regulated through various mechanisms, such as the obligation to fulfill TKDN, to the requirements for Trade, Local Content, and Offsets (IDKLO) in the procurement process for the import of Defense and Security Protection. On the other side, efforts to establish a more competitive industrial ecosystem are also being carried out by the Government in stages through the implementation of the Defense Industry Independence Grand Design, as well as encouraging the implementation of a diversification strategy and optimizing the dual-use strategy in increasing competitiveness, as well as supporting industry continuity.